HUBUNGAN PENDIDIKAN KARAKTER DENGAN KECERDASAN EMOSIONAL SISWA DI SEKOLAH SMA NEGERI 4 BANGKO PUSAKO KABUPATEN ROKAN HILIR - Tika Tika; Hambali Hambali; Haryono Haryono (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This study aims to determine the relationship between character education and emotional intelligence of students in SMA Negeri 4 Bangko Pusako. The formulation of the problem in this study is